Interpreting Integrity: A Qualitative Approach. (4th March 2023) - Carr, Danny Nathaniel
Abstract: There have been calls by the academic community for more efforts to conceptualize integrity using empirical works in a range of contexts, and using different methodological and theoretical approaches. Conceptualizing integrity using empirical works can be especially important since the way integrity is conceptualized can improve or hinder the way corruption is understood and may even strengthen or weaken explanations on why anti-corruption efforts tend to be unsuccessful. This study attempts to answer this call by using a case study approach to gather qualitative data on the perspectives of politicians in the Caribbean region. In-depth interviews with eight politicians in Trinidad and Tobago were conducted. The study builds on the conceptual framework of moral emotions and reciprocal altruism as posited by Haidt and aims to produce a conceptualization of integrity that reflects the meanings and ideas of the term as expressed by the research participants. The study will also attempt to explore integrity from both an individual level approach and an organizational level approach by incorporating ideas from sociological theorizing. The study ends by discussing the implications of the findings in terms of how integrity and corruption are understood.